Moose survey app for population monitoring. (11th March 2017) - Boyce, Mark S.; Corrigan, Rob
ABSTRACT: We developed a smart phone app for hunters to report the number of moose ( Alces alces ) observed while hunting in Alberta, Canada, during 2012–2014. Excessive costs of aerial surveys often result in infrequent estimates of moose abundance, whereas hunter observations can be obtained for minimal expense. Correlations of the number of moose observed by hunters with hunter success, moose harvests, and aerial survey estimates of abundance suggest that the method offers promise as an alternative to aerial ungulate surveys. Engaging hunters with the Moose Survey app has potential to increase the spatial extent and temporal frequency of monitoring with benefits for harvest management. © 2017 The Wildlife Society. Abstract : High costs of aerial surveys of moose populations prompted development of a smartphone app for hunters to record the number of moose seen while hunting. Counts of moose seen by hunters were highly correlated with moose abundance validating the app as a tool for monitoring.